TRANSFORMASI DEMOKRASI INDONESIA: PENGHAPUSAN PRESIDENTIAL THRESHOLD DALAM PANDANGAN HUKUM PROGRESIF - Djafar, Mohammad Ali Akbar; Suleman, Frangki (Datuk Sulaiman Law Review (DaLRev), 2025)
The purpose of this study is to analyze the impact of the implementation of the Presidential Threshold system on Indonesian elections, and how a progressive legal perspective can influence the policy in the context of a more inclusive and just democracy. This study also aims to explore the elimination of the presidential threshold on government stability and political representation in Indonesia. The method used is normative legal research with a descriptive and interpretative approach, including guidelines for legislation, and context analysis. Legal materials are collected through literature studies, which include primary and secondary legal documents, and related sources. The results of the study indicate that although the Presidential Threshold system plays a role in strengthening government stability, this policy also limits the opportunities for small parties to participate in presidential elections, reduces the diversity of political aspirations, and can activate social polarization. From a progressive legal perspective, the elimination of the Presidential Threshold can increase political inclusiveness, although it has the potential to cause greater fragmentation in the Indonesian political system. Therefore, this threshold needs to be considered carefully to achieve a balance between social justice, political representation, and effective government stability.